Analysis of degree courses in Rural Education in the northeast region and training for deaf education - Adriana Farias do Nascimento; ANA CRISTINA SILVA DAXENBERGER (Universidade Federal do Norte do Tocantins, 2024)
The general objective of the research is to map and identify which are the Universities and Federal Institutes of the northeast region that offer the Licentiate Degree in Rural Education course, and if the subject of Brazilian Sign Language (Libras) is included in the curricular matrix of the course, in addition to to analyze the contents presented in the curricular component through its teaching programs. The research data were analyzed in the light of the legal and theoretical foundations that defend the education of the deaf and social and school inclusion, as well as scholars of rural Education. The research has a qualitative character, being characterized as a bibliographical and documental research. Data were analyzed descriptively and interpretively by mapping Federal public institutions in the northeast region. It was found that the presence of the Libras discipline in the Degree in Education courses in the countryside is predominant, and the discipline syllabi emphasize theoretical knowledge about the language, as well as aspects involving the current legislation. However, the presence of the discipline in the course does not guarantee the full linguistic development of the teacher in formation, being necessary a continuous formation to satisfactorily develop the sign language.